Synthesis and characterization of CeVO4 by microwave radiation method and its photocatalytic activity - Nuengruethai Ekthammathat (2018)
A general microwave synthesis method was developed to synthesize cerium orthovanadate (CeVO 4 ) nanostructures without the use of any catalysts or templates. This method is able to control the shape and size of the products by adjusting the pH of precursor solutions to be 1-10. Phase, purity, and different morphologies of the products were characterized by XRD, FTIR, SEM, and TEM. They showed that the as-synthesized products exhibited pure single crystalline CeVO 4 with tetragonal structure. Their morphologies developed in sequence as nanoparticles (pH = 4-10), nanorods (pH = 2, 3), and microflowers (pH = 1). UV-visible spectra were used to estimate the direct energy gaps of CeVO 4 nanorods and microflowers: 3.77 and 3.65 eV, respectively. Photoluminescence (PL) of CeVO 4 microflowers showed strong emission intensities at 578 nm. These results were in the range of possible application for photocatalysis, investigated by studying the degradation of methylene blue. © 2013 Nuengruethai Ekthammathat et al.